The EU and conflict resolution [ promoting peace in the backyard - Tocci, Nathalie (Routledge/UACES contemporary European studies series, 2007)
Through the study of five ethno-political conflicts lying on or just beyond Europe's borders, this book analyzes the impact and effectiveness of EU foreign policy on conflict resolution. Taking a comparative approach, it explores the principal determinants of conflict dynamics in Cyprus, Turkey, Serbia-Montenegro, Israel-Palestine and Georgia